2019
DOI: 10.3390/ijerph16244944
|View full text |Cite
|
Sign up to set email alerts
|

Association between Changes in Depressive State and Cognitive Function

Abstract: Dementia is defined as a severe form of cognitive impairment. Research concerning the two-way relationship between depression and cognitive impairment has been conducted; however, there has been little analysis of cognitive function following changes in depressive status. This study describes the association between changes in depressive state and cognitive function in a Korean geriatric population sample. Using the Korean Longitudinal Study of Aging (KLoSA) database, Mini-Mental State Examination (MMSE) score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The recruitment of participants and methods used in MHAS and KLoSA have been described in detail elsewhere( Borda et al, 2019 ; Kim, Kim, Kwon, & Park, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The recruitment of participants and methods used in MHAS and KLoSA have been described in detail elsewhere( Borda et al, 2019 ; Kim, Kim, Kwon, & Park, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was made on wave 2016. The recruitment of participants and methods used in KLoSA have been described in detail elsewhere [13,14]. See the flowchart of the total population in Fig.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…In terms of physical health, studies have found that physically active older adults have a lower risk of disability, functional limitations, and cognitive decline ( 24 ), and there is a negative correlation between the number of chronic diseases and cognitive decline ( 25 ). And when it comes to mental health, some studies have shown that symptoms of depression and anxiety can lead to cognitive decline ( 26 , 27 ), and the quantity and quality of sleep conditions will change with the increase of age, and lack of sleep conditions will lead to decreased cognitive function ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%